The Early Cities of the Islamic World: Kufa and Basrah (A Study of the Historical Formation and Social Condition): Kota Awal Dunia Islam: Kufah dan Basrah (Studi Terhadap Sejarah Pembentukan dan Kondisi Sosialnya) - Fatianda, Septian; Hasanah, Ida; Agustina, Lisa; Fitriani (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
The policy of expanding territory was an imperative aspect of the early days of Islamic rule in Medina. The main reason Islamic leaders sought to expand their territory into regions such as Persia and mainland North Africa was to further the interests of da’wah. History records indicate that Islamic troops succeeded in establishing new settlements, which later became centres of new civilization, in addition to the cities of Mecca and Medina. Notably, these new cities included Kufa and Basrah. This research employs historical methods, specifically a library study approach, to locate historical data. The four methods utilized are heuristics, verification, interpretation, and historiography. The research findings show that these four cities were chosen because of their strategic locations as the leading fronts for the mission to conquer territory under the power of Islamic enemies such as Persia. In these cities, Muslims began to build new city plans until they developed into centres for trade, agriculture, and the military. As a result, outsiders began to settle and formed a new social identity in these cities.